Innovative Strategy for Strengthening Quran Memorization Through Differentiated Learning in Islamic Religious Education and Character Education - Rahmawati, Rahmawati; Wirasti, Murti Kusuma; Paristiowati, Maria (Green Publisher Indonesia, 2026)
Islamic Religious Education (PAI) faces challenges in adapting to diverse student learning needs, particularly in Quran memorization. Preliminary surveys indicate that 60% of PAI teachers rely on lecture methods, 80% use PowerPoint media, and 52.4% of students report difficulty memorizing Quran verses due to ineffective strategies. This study addresses the gap between conventional teaching approaches and the need for personalized memorization strategies responsive to students’ varied learning styles. Using the Dick and Carey Research and Development (R&D) model, this study develops a differentiated learning product for Quran memorization tailored to visual, auditory, and kinesthetic learning preferences. The research was conducted at SMA Labschool Jakarta, involving PAI teachers and Grade XII students through expert validation, one‑to‑one trials, small‑group trials, and field trials. Feasibility testing yielded a score of 3.56 (very practical), and formative evaluation averaged 3.65 (very practical). Effectiveness testing using a paired‑sample t‑test showed a significant increase in memorization scores from pre‑test (mean = 91.60) to post‑test (mean = 95.95) with p < 0.05. The differentiated learning approach, which differentiates content, process, and product, successfully accommodated student diversity and improved memorization outcomes. This research contributes an innovative, evidence‑based strategy for PAI learning that integrates Quran memorization with differentiated instruction principles, offering practical guidance for teachers to address diverse student needs.